Serotonin receptor expression in hippocampus and temporal cortex of temporal lobe epilepsy patients by postictal generalized electroencephalographic suppression duration. Issue 11 (5th September 2022) - Leitner, Dominique Frances; Devore, Sasha; Laze, Juliana; Friedman, Daniel; Mills, James D.; Liu, Yan; Janitz, Michael; Anink, Jasper J.; Baayen, Johannes C.; Idema, Sander; van Vliet, Erwin Alexander; Diehl, Beate; et al.
Abstract: Objective: Prolonged postictal generalized electroencephalographic suppression (PGES) is a potential biomarker for sudden unexpected death in epilepsy (SUDEP), which may be associated with dysfunctional autonomic responses and serotonin signaling. To better understand molecular mechanisms, PGES duration was correlated to 5HT1A and 5HT2A receptor protein expression and RNAseq from resected hippocampus and temporal cortex of temporal lobe epilepsy patients with seizures recorded in preoperative evaluation. Methods: Analyses included 36 cases (age = 14–64 years, age at epilepsy onset = 0–51 years, epilepsy duration = 2–53 years, PGES duration = 0–93 s), with 13 cases in all hippocampal analyses. 5HT1A and 5HT2A protein was evaluated by Western blot and histologically in hippocampus ( n = 16) and temporal cortex ( n = 9). We correlated PGES duration to our previous RNAseq dataset for serotonin receptor expression and signaling pathways, as well as weighted gene correlation network analysis (WGCNA) to identify correlated gene clusters. Results: In hippocampus, 5HT2A protein by Western blot positively correlated with PGES duration ( p = .0024, R 2 = .52), but 5HT1A did not ( p = .87, R 2 = .0020). In temporal cortex, 5HT1A and 5HT2A had lower expression and did not correlate with PGES duration. Histologically, PGES duration did not correlate with 5HT1A or 5HT2A expression in hippocampal CA4, dentate gyrus, or temporal cortex. RNAseq identified two serotonin receptors with expression that correlated with PGES duration in an exploratory analysis: HTR3B negatively correlated ( p = .043, R 2 = .26) and HTR4 positively correlated ( p = .049, R 2 = .25). WGCNA identified four modules correlated with PGES duration, including positive correlation with synaptic transcripts ( p = .040, Pearson correlation r = .52), particularly potassium channels ( KCNA4, KCNC4, KCNH1, KCNIP4, KCNJ3, KCNJ6, KCNK1 ). No modules were associated with serotonin receptor signaling. Significance: Higher hippocampal 5HT2A receptor protein and potassium channel transcripts may reflect underlying mechanisms contributing to or resulting from prolonged PGES. Future studies with larger cohorts should assess functional analyses and additional brain regions to elucidate mechanisms underlying PGES and SUDEP risk.